The Manly Modern: Masculinity in Postwar Canada - Fahrni, Magda (Labour / Le Travail, 2008)
The article reviews the book, "The Manly Modern: Masculinity in Postwar Canada," by Christopher Dummitt.
Keywords: BOOKS -- Reviews; DUMMITT, Christopher; MANLY Modern: Masculinity in Postwar Canada, The (Book); Masculinity; Nonfiction